Show that





Differentiating both sides with respect to x, we get:

$2 y \frac{d y}{d x}=a(-2 x)$

$\Rightarrow 2 y y^{\prime}=-2 a x$


$\Rightarrow y y^{\prime}=-\alpha x$            ...(1)

Again, differentiating both sides with respect to x, we get:

$y^{\prime} \cdot y^{\prime}+y y^{\prime \prime}=-a$

$\Rightarrow\left(y^{\prime}\right)^{2}+y y^{\prime \prime}=-a$                       ...(2)

Dividing equation (2) by equation (1), we get:

$\frac{\left(y^{\prime}\right)^{2}+y y^{\prime \prime}}{y y^{\prime}}=\frac{-a}{-a x}$

$\Rightarrow x y y^{\prime \prime}+x\left(y^{\prime}\right)^{2}-y y^{\prime \prime}=0$

This is the required differential equation of the given curve.




Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now